Characterization of Activated Carbons from Oil-Palm Shell by CO2 Activation with No Holding Carbonization Temperature - S. G. Herawan; M. S. Hadi; Md. R. Ayob; Putra, Azma (Hindawi, 2013)
Activated carbons can be produced from diferent precursors, including coals of diferent ranks, and lignocellulosic materials, by physical or chemical activation processes. he objective of this paper is to characterize oil-palm shells, as a biomass byproduct from palm-oil mills which were converted into activated carbons by nitrogen pyrolysis followed by CO2 activation. he efects of no holding peak pyrolysis temperature on the physical characteristics of the activated carbons are studied. he BET surface area of the activated carbon is investigated using N2 adsorption at 77K with selected temperatures of 500, 600, and 700∘ C.hese pyrolysis conditions for preparing the activated carbons are found to yield higher BET surface area at a pyrolysis temperature of 700∘ C compared to selected commercial activated carbon. he activated carbons thus result in well-developed porosities and predominantly microporosities. By using this activation method, signiicant improvement can be obtained in the surface characteristics of the activated carbons. hus this study shows that the preparation time can be shortened while better results of activated carbon can be produced.